The Effects of Manipulating Task Difficulty and Feedback Frequency on Children's Dart Throwing Accuracy and Consistency. - Bahri, Fatma; Elghoul, Yousri; Masmoudi, Liwa; Clark, Cain C. T.; Glenn, Jordan M.; Souissi, Nizar (Perceptual & Motor Skills, 2021)
In the present study we investigated the effects of manipulating task difficulty (constant vs. progressive difficulty) and frequency of knowledge of results (KR) on the accuracy and consistency of children's performance of a novel fine motor coordination task (dart throwing). We assigned 69 right-handed physical education (PE) students (M age = 10.73, SD = 0.89 years) to progressive (PDG) or constant difficulty (CDG) groups. PDG and CDG were each split into three subgroups who received varying KR frequency (100%KR, 50%KR, and 33%KR), creating a total of six groups. We increased difficulty in the PDG by manipulating the distance to the target (2 m, 2.37 m, and 3.56 m), while distance to the target was constant for CDG throughout the experiment (2.37 m). We conducted performance assessments during familiarization (pre-test), acquisition (post-test), and retention (retention testing) learning phases under both normal condition (NC) and a time pressure condition (TPC). Repeated-measures analysis of variance revealed a significant effect of difficulty manipulation on skill learning under both NC and TPC. Further analyses revealed that skill learning was enhanced by progressive difficulty manipulation. However, learning was not affected by KR frequency changes. Progressive difficulty practice enhanced both accuracy and consistency, specifically at retention testing. These results suggest that motor learning in children may be enhanced by practicing with progressive increases in difficulty. PE teachers are encouraged to gradually introduce difficulty levels in motor learning tasks that require high accuracy.